Oligonucleotides for the identification of staphylococcus aureus. - Shamsudin, Mariana Nor; Rajah, V. Neela (2006)

(untitled)
The present invention provides a rapid and simple method for the detection of Staphylococcus aureus in a biological sample. Accordingly, the present invention discloses oligonucleotide primers and probe in a polymerase chain reaction for specific amplification and detection of a Staphylococcus aureus target nucleotide sequence. The invention also relates to a diagnostic kit comprising the primers, probe and optimized methods disclosed in the present invention are capable of specifically detecting Staphylococcus aureus in a rapid manner.